Establishing Students' Environmental Care Character At The Adiwiyata School In The Framework Of Education For Sustainable Development (ESD) - Sari, Hilda Putri; Chandra, Edy; Roviati, Evi (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2021)
This study aims to analyze students' environmental care character and the obstacles faced by the Adiwiyata school. This study employed the descriptive qualitative method with the case study approach. The researchers analyzed the students' environmental care character with the Adiwiyata program, specifically SMAN 1 Dukuntang. In the aspect of classroom hygiene management, the school was in the very good category. Next, in the environmental education management aspect, the school was also in the very good category. The school also foster students' creativity through the DLS program by creating environmentally friendly products with economic value. The obstacle faced by the Adiwiyata school in shaping the students' environmental care character was the need for free time for students to participate in environmental activities outside of school during the implementation of the SBL program.